Do Social Media Platforms Have Free Speech Rights to 'Censor' Conservatives? - Samuelson, Pamela (Communications of the ACM, 2024)
The article discusses how the U.S. Supreme Court addressed challenges to Florida and Texas laws prohibiting censorship by social media platforms which moderated user content, particularly targeting claims of bias against conservative viewpoints. In NetChoice v. Moody and NetChoice v. Paxton, the Court affirmed that platforms have First Amendment rights akin to editorial discretion, allowing them to curate or exclude content. While the Court sent the cases back to lower courts for further examination of evidence and the laws’ scope, it emphasized that government efforts to regulate content moderation or impose viewpoint-based restrictions are constitutionally suspect.